PERAN KEPALA DESA DALAM PENGELOLAAN SAMPAH PADA MASYARAKAT DUSUN BATMAN - Eli Herlina (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2019)
This research aims to know how the role of the village head in managing waste and the impact of the role of the village head who was in the Batman hamlet in applying to the community about waste management properly and becoming a clean and healthy environment. This research was a qualitative descriptive approach to the type of qualitative research. Data collection techniques were observation, interviews and documentation. Data analysis technique was interactive model qualitative data analysis through the stages of data reduction, data presentation, and data verification. It can be reported that the village head has three roles in managing waste in the Batman hamlet in Selaparang village, namely as a provision of funds, as a regulator and as an implementer, and there are also positive and negative impacts on the role of the village head for the community, from social aspects, environmental aspects, and economic aspects.